ナンキョク バンダ コ ニ オケル サイキン ノ サイボウ サイズ ト ゲンゾン リョウ ノ スイチョク ブンプ - 近田, 俊文; コンダ, トシフミ; 滝井, 進; タキイ, ススム; 福井, 学; フクイ, マナブ; 楠岡, 泰; クスオカ, ヤスシ; 松本, 源喜; マツモト, ゲンキ; 中谷, 周; ナカヤ, シュウ; et al. (1987)
P(論文) 南極ドライバレー地域のバンダ湖における細菌の垂直分布について, 1984年12月にアクリジンオレンジ染色による直接計数(AODC)法を用いて調べた結果を, 1984年1月の調査結果(S.TAKII et al. : Hydrobiologia, 135,15,1986)と比較した。湖水中の細菌数・細胞サイズ・現存量の垂直分布パターンは, 両調査時期でよく類似していた。すなわち, 全菌数(AODC)は, 水深55m以浅では(10)^4cells/mlのオーダーであったが, それ以深で急激に増加して, 底層水(69m)では5.0×10^6cells/mlに達した。細菌の細胞サイズについてみると, 5m層から60m層までは長さ1.0-2.0μmの桿菌が最も多く, 特に水深55m以浅では長さ10μm以上の糸状細菌も比較的多く出現したが, 水深65m以深では長さ1.0μm以下の球桿菌や短桿菌がほとんどであった。細菌体積量から炭素量に換算した細菌現存量は, 0.0026-0.079mgC/lの範囲であった。 Vertical distribution of bacteria in Lake Vanda in the Dry Valleys region of the Antarctic was examined by the acridine orange direct count (AODC) method in December 1984 and the results were compared with those of January 1984 (S. TAKII et al. : Hydrobiologia, 135,15,1986). Bacterial numbers, cell sizes, and biomass in the water showed an almost identical pattern of vertical distribution at the two sampling times. Total bacteria by the AODC method were in the order of 10^4cells/ml in the water at the depth of 55m and above, and increased markedly to 5.0×10^6cells/ml in the bottom water (69m depth). Bacteria from the water between 5 and 60m depths were dominated by rods of 1.0-2.0μm length, and, particularly, filamentous bacteria more than 10μm long occurred a relatively high frequency in the water above the depth of 55m. On the other hand, most bacteria from the water at depths below 65m were coccoidal or short rods less than 1.0μm long. Bacterial biomass estimated from cell volumes ranged from 0.0026 to 0.079mgC/l. departmental bulletin paper